The Implementation of International Legal Standards in the Investment Legislation of Uzbekistan - Nodira, Yunusova; Ling, Zhai Yun (Richtmann Publishing, 2012)
This research seeks to identify distinctive inhibitions in the implementation of international legal; standards in internationallaws of Uzbekistan. This study is necessitated by the continued disparity between implementation of international commerce laws andtheir dismal efficiency in draw foreign investment. Despite the country’s effort towards enforcement of international trade laws, there ispersistent low FDI in the country compared to other central Asia countries. This is happening despite the central placing of Uzbekistan inthe region, the superior human resource base, compared to its neighbors, and the expansive indigenous resources in the country. Thishighlights the need to identify the cause of these inhibitive phenomena. In sight of decreasing GDP and the global continued pressure onfossil energy, more investment in oil the nation is a priority. Western investors are not eager to invest in the country, while trade volumeswith china are low. This study focuses on relationship between Uzbekistan and PRC. A proposed cause of this problem was thedisproportion between the domestic laws in both countries. The researcher evaluates the possibility of the differences in the source andnature of domestic laws in both countries as being an inhibitor in the development of effective international investment law that meetinternational standards, and are efficient in attracting FDI. The research employs comparative law research methodology. This involvesthe evaluation of the two legal systems, and identifying disparities in local laws that could be detrimental to effective implementation ofinternational law